Shikimate accumulation, glyphosate absorption and translocation in horseweed biotypes - CARDINALI,V.C.B. (2015)
In Brazil, few research works on mechanisms of weed resistance to glyphosate have been conducted so far. Therefore, this research aimed to study analytical procedures determining the relation between the concentration of plant shikimate after glyphosate application and the plant resistance to this herbicide; and evaluate the glyphosate absorption and translocation into two resistant ® and susceptible (S) horseweed biotypes to glyphosate. Horseweed plants with nine true leaves received glyphosate (720 g a.e. ha-1), and 2, 3, 4, 7 and 10 days after application (DAA) the concentration of shikimic acid was measured by HPLC. In another experiment, plants were treated with radiolabeled glyphosate (14C) (1.456 MBq mmol-1 specific activity) and radioactivity was measured 4, 8, 24, 48 and 72 hours after treatment (HAT) by liquid scintillation spectrometry. The shikimate concentration in plants increased 16,351.14 and 7,892.25 mg kg-1 of dry weight, for R and S plants respectively, at seven DAA. Therefore, the procedure for quantification of shikimic acid was suitable for R and S plants differentiation to glyphosate, indicating that the R population is actually resistant to glyphosate. On average, 98% of glyphosate applied was absorbed by the studied biotypes, at 72 HAT. Around 68% of the absorbed radioactivity remained on the biotypes leaves treated, the S biotype showing the highest translocation. Therefore, the R biotype resistance mechanism studied is associated to the differential translocation.